Review artikel: validasi metode analisis kafein dalam minuman kemasan menggunakan berbagai instrumen - Maesarah, Siti; Permatasari, Lina (Sasambo Journal of Pharmacy, 2025)
Caffeine is a central nervous system stimulant that is commonly found in packaged beverages. While moderate consumption provides cognitive and physical benefits, excessive intake may cause adverse health effects, including anxiety disorders, insomnia, cardiovascular diseases, and renal dysfunction. Consequently, accurate and validated analytical methods are essential for determining caffeine levels in commercial beverages. This review evaluates analytical instruments and techniques for caffeine quantification, drawing on national and international studies published between 2015 and 2025. The methods examined include UV-Visible Spectrophotometry, High-Performance Liquid Chromatography (HPLC), Gas Chromatography–Mass Spectrometry (GC–MS), Ultra-Performance Liquid Chromatography (UPLC), and High-Performance Thin-Layer Chromatography (HPTLC). Validation was assessed using parameters such as limit of detection (LOD), limit of quantification (LOQ), precision, accuracy, and linearity. The findings indicate that all methods meet acceptable validation criteria. Among them, UPLC demonstrated the highest sensitivity, while HPTLC provided advantages in speed and operational efficiency. Therefore, the choice of method for caffeine determination should be guided by analytical objectives, laboratory resources, and required sensitivity.